Strategi Komunikasi Persuasif Ustadz Dalam Meningkatkan Motivasi Orang Tua Untuk Belajar Baca Alqur’an Di LPQ Al-Maghfirah Kota Gorontalo - Bakir, Mega Putri Aulia; Tamu, Yowan; Kaharfin, La Here (Jambura Jurnal Ilmu Komunikasi, 2025)
This study explores the persuasive communication of the ustadz in increasing parents' motivation to learn how to read the Quran. The study utilized a qualitative method with a descriptive approach to explain the data obtained through observation, interviews, and documentation. Data analysis was conducted using the interactive model developed by Miles and Huberman. The findings indicate that parents’ motivation to learn Qur’an reading stems from both intrinsic and extrinsic motivations. Furthermore, parents’ willingness to participate in the Qur’an reading program at LPQ Al-Maghfirah is attributed to the persuasive approach adopted by the ustadz, which involves stages of capturing attention, generating interest, fostering desire, facilitating decision-making, and encouraging action to join the program. Additionally,the increase in parents’ learning motivation was examined from cognitive, affective, and conative aspects. Therefore, the motivation to learn Qur’an reading can be attributed significantly to the role of the ustadz in persuading parents through various strategies, which effectively enhances their interest in learning